2020
DOI: 10.1080/23802359.2020.1787259
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding elucidates the new altitude record and range-extension of lesser-known bullfrog (Hoplobatrachus litoralis) in northeast India

Abstract: The molecular information of lesser-known bullfrog, Hoplobatrachus litoralis is restricted from Bangladesh (type locality) and Myanmar. The morphological observation further evidenced the rangeextension of this species from India and Myanmar. Here, we collected the H. litoralis specimen from the Dampa Tiger Reserve, Mizoram state and provides a new altitude record (268 m) and range-extension in northeast India. The DNA barcoding with mitochondrial Cytochrome b gene discriminates H. litoralis from other congene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The tree revealed monophyly of each Hoplobatrachus species and the authors suggested that the environment specific to the river system (riverine delta region) has sustained the H. tigerinus population structure in this region. Kundu et al (2020) provided an updated distribution of H. litoralis in the Dampa Tiger Reserve, Mizoram state, northeast India, based on morphological and molecular data, where the BI phylogenetic tree revealed monophyly of five Hoplobatrachus species (H. crassus, H. tigerinus, H. litoralis, H. rugulosus, H. occipitalis) and a sister relationship was presented between H. litoralis and H. tigerinus. Nevertheless, Hoplobatrachus specimens from Myanmar (Bago and Yangon in Mulcahy et al, 2018) and Thailand were not included in the work of Kundu et al (2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tree revealed monophyly of each Hoplobatrachus species and the authors suggested that the environment specific to the river system (riverine delta region) has sustained the H. tigerinus population structure in this region. Kundu et al (2020) provided an updated distribution of H. litoralis in the Dampa Tiger Reserve, Mizoram state, northeast India, based on morphological and molecular data, where the BI phylogenetic tree revealed monophyly of five Hoplobatrachus species (H. crassus, H. tigerinus, H. litoralis, H. rugulosus, H. occipitalis) and a sister relationship was presented between H. litoralis and H. tigerinus. Nevertheless, Hoplobatrachus specimens from Myanmar (Bago and Yangon in Mulcahy et al, 2018) and Thailand were not included in the work of Kundu et al (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Kundu et al (2020) provided an updated distribution of H. litoralis in the Dampa Tiger Reserve, Mizoram state, northeast India, based on morphological and molecular data, where the BI phylogenetic tree revealed monophyly of five Hoplobatrachus species (H. crassus, H. tigerinus, H. litoralis, H. rugulosus, H. occipitalis) and a sister relationship was presented between H. litoralis and H. tigerinus. Nevertheless, Hoplobatrachus specimens from Myanmar (Bago and Yangon in Mulcahy et al, 2018) and Thailand were not included in the work of Kundu et al (2020). The current results showed that H. salween sp.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been useful to understand the geographical distributions of populations, providing insights into the patterns of geneflow within a species (Hajibabaei et al 2007). Using DNA barcoding, many studies have identified the new extent of the species thus expanding their distribution range (Seshadri et al 2016;Kundu et al 2020;Lim et al 2020).…”
Section: Introductionmentioning
confidence: 99%